How much does financial development contribute to renewable energy growth and upgrading of energy structure in China? - Ji, Qiang; Zhang, Dayong (Energy policy, 2019)
Developing renewable energy sector and upgrading energy structure have strategically important role in China's commitments against climate changes. Policymakers and authorities have put forward great efforts to make them happen. But one of the key constraints of China's energy revolution is financial issues, which is inevitably linking to the country's financial development. It is of great importance to understand how much financial development contributes to the renewable energy development in China, and more importantly what aspects of financial development matter. Through a time series analysis based on macro-level data, this paper provides clear evidence that financial development is critically important and contributes an overall of 42.42% to the variation of renewable energy growth. Specifically, we are able to demonstrate that capital market is the most important factor, followed by foreign investment. A simple comparison to the EU and the US cases indicates that the EU path is more relevant and should be studied more carefully by the Chinese policymakers. •Effective policies are needed for upgrading energy structure to cope with climate changes.•Financial sector is critically important for China to development renewable energy.•Capital market has the most important impact followed by foreign investment.•The EU development path is more relevant to the energy revolution in China.